PENGGANDAAN SKALA PRODUKSI INSEKTISIDA HAMA WERENG COKELAT KAPASITAS 25 DAN 1000 LITER SERTA PELUANGNYA DI DUNIA INDUSTRI - Muh. Agus Ferdian (AGROINTEK, 2021)
The downstream of DEA surfactant products has great potential in the industrial world, one of which is agricultural product in the form of insecticides. The purpose of this study is to examine the scale multiplication of insecticide products for the brown planthopper on a pilot scale of 25 l and an industrial scale of 1000 l and calculating the selling price of insecticide products with different profit variations based on the cost of production. The scale multiplication was based on the unit of power per unit volume (Pg /V) which had a fixed value. The optimal agitation speed in product formation was obtained from a small-scale experiment, and the results were used to obtain the agitation speed on a large scale, which required the same power per unit volume. A simple step to calculate multiplication of the scale was by using the basic geometric shape of the tools used in the process performed. The determination of the tools used was based on the effectiveness of the two types of tools, namely mixer and homogenizer. Furthermore, the multiplication of the scale into geometric shapes on the scale of 25 l was carried out and continued on the scale of 1000 l. The required parameters in determining the geometry of the reactor were impeller diameter (Di), tank diameter (Dt), sample of liquid height (HL), impeller rotation (Ni). The results obtained showed that the effectiveness of insecticide production was higher in the use of this type of homogenizer tool. In this study, the power per unit volume (Pg /V) was fixed. Calculation data obtained from the laboratory scale include Ht; HL; Di and Dt. On the scale of 25 L were 28.2; 19.5; 12.2 and 33.6 cm, meanwhile on the scale of 1000 L were 95.7; 66.9; 41.7 and 115.4 cm. The result of the calculation of the impeller rotation speed at a scale multiplication of 1000 L was 396 rpm. The calculation of the selling price of the brown planthopper insecticide per bottle (200 ml) for the 50% profit margin was IDR 13,043, the 100% profit margin was IDR 17,390 and the 200% profit margin was IDR 26,086.